2018
DOI: 10.1111/jacf.12296
|View full text |Cite
|
Sign up to set email alerts
|

The ESG Integration Paradox

Abstract: Today, most investment managers have something to say about environmental, social and governance (ESG) issues, and written ESG policies are ubiquitous. Yet, a written policy is not a reliable indicator of a firm's commitment. Actual ESG incorporation practices vary greatly, with most investment managers falling well short of full integration. Only a few firms seem to be using ESG factors to deliver alpha, hence, the paradox. If not implemented wholeheartedly, responsible investing can lead to lower financial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 0 publications
1
42
0
2
Order By: Relevance
“…We applied these criteria to the ISI Web of Science, specifically searching for any paper whose title, abstract or keywords included "private equity" and "ESG". The database search returned only four responses [40][41][42][43]. Since only a few studies have been found in this limited area, we decided to explore the field by interviewing ESG and PE experts.…”
Section: Methodsmentioning
confidence: 99%
“…We applied these criteria to the ISI Web of Science, specifically searching for any paper whose title, abstract or keywords included "private equity" and "ESG". The database search returned only four responses [40][41][42][43]. Since only a few studies have been found in this limited area, we decided to explore the field by interviewing ESG and PE experts.…”
Section: Methodsmentioning
confidence: 99%
“…While transition preparedness analysis is possible with an active approach, unfortunately only very few do it (Cappucci 2017;Mooij 2017b). Ironically, part of the reason is that the low relevance of ratings has made many analysts overly sceptical of ESG.…”
Section: Achieving a Change In Mindsets And Methodsmentioning
confidence: 99%
“…12. Cappucci (2018) has noted that most firms 'pay heed to sustainable investment principles while demonstrating a less than plenary commitment to ESG practices', the cause of which (among others) is a lack of standardized ESG performance evaluation. 13.…”
Section: Notesmentioning
confidence: 99%